English: Bahasa Indonesia - Muhammad Nurul Alim; Djaka Suryadi; Farhan Kamiluloh (IQTISHODUNA: Jurnal Ekonomi Islam, 2022)
This study aims to propose a model of sukuk-wasiyyah. Since waqf fundraising is one of the activities of waqf management, this model applies wasiyyah or the will of waqif to sukuk. Wasiyyah will restrict the use of the fund by the will of Musi while sukuk is one of the Islamic capital market instruments. Like cash waqf, the fund of sukuk-wasiyyah will be managed by nazhir and its profit can be spent on Islamic philanthropy. This study applies exploratory research. The result of the study shows that (1) Musi or the bequeath testator still can gain the sukuk return during his life, (2) After Musi died, the sukuk is transferred under custody by Nazir. The author argues that the proposed product applies to Waqf Institution. This study is the first to introduce the terms of sukuk-wasiyyah and to propose the mechanism of sukuk-wasiyyah in the Islamic capital market